Quantitative correlation between Flash and equivalent transistor for endurance electrical parameters extraction. (September 2018) - Della Marca, V.; Postel-Pellerin, J.; Kempf, T.; Regnier, A.; Chiquet, P.; Bocquet, M.
Abstract: Nowadays, the study of physical mechanisms that occur during Flash memory cell life is mandatory when reaching the 40 nm and beyond nodes in terms of reliability. In this paper we carry out a complete experimental method to extract the floating gate potential evolution during the cell aging. The dynamic current consumption during a Channel Hot Electron operation for a NOR Flash is a proper quantitative marker of the cell degradation. Here both drain and bulk currents are measured and monitored throughout the endurance tests. We coupled these characteristics with quasi-static measurements to correlate the cell degradation with an equivalent transistor. The final goal is to be able to split the physical effects of repetitive hot carrier and Fowler-Nordheim operations, typical of Flash memories, to extract the electrical parameters evolution on a simple equivalent transistor. Highlights: Flash floating gate reliability and current consumption. Combination of electrical characterization on memory and equivalent transistor for smart algorithm generation. Impact of tunnel oxide degradation on dummy cell electric parameters. The source current consumption is used as a marker of cell degradation.